Human Relations in the Prophet’s Era and its Jurisprudential Impact on Coexistence: The Case of Ibn Urayqat is a Model - Alhelalat, Mohammad Muhaisen Mohammad (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This research aims to highlight the positive relationships in Islam with others by exploring the social and economic relations during the Prophetic era and comparing them to the present day. It seeks to emphasize the role of historical jurisprudence in fostering peaceful coexistence, as its significance lies in dispelling misconceptions, improving relationships, and strengthening faith in the message of Islam. Methods: Ibn Arīqat was selected as a model due to the strong significance of his incident in supporting the study’s objectives. The analysis of Ibn Arīqat’s case was conducted inductively, breaking down the event into its components. This specific incident was used as evidence for similar events, employing a priority analogy. Results: The research identified the primary methods of social acquaintance during the Prophetic era as lineage, description, and religion, and the main methods of social security as alliances, protection, geographical knowledge, communal travel, and migration. The study affirmed that these methods persist in the modern era, albeit in more complex forms. Furthermore, it demonstrated that the case of Ibn Arīqat is central to understanding the contract of hiring (ijārah) and that trustworthiness is the key criterion in social transactions. The research also concluded that religious differences do not preclude cooperation in society and that relationships during the Prophetic era were amicable with peaceful individuals, as Islamic jurisprudence has outlined the methods of peaceful coexistence. Conclusion: The incident revealed various social, economic, and psychological behaviors that preserve both the individual and society, such as hospitality and diligent work ethics. The study recommends further investigation into the lives of migrants, the correlation between attention to lineage and crime rates, and the impact of ambiguous contracts on contemporary economic crises.